The Effect of HR Quality on the Compensation System and Employee Performance at PT Primissima in Sleman Regency - Satrio Nugroho, Wahyu; Ayu Setyaning, Alldila Nadhira; Adhi Pradana, Handrio (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The lack of quality human resources at work is the main problem highlighted by PT Primissima located in Sleman Regency, Yogyakarta. In order to have superior, resilient human resources, and be able to maintain the existence of competitiveness and brand equity in the market, the company must be able to guarantee the performance of its human resources while working in the company. With appropriate compensation, HR will be able to work optimally and company goals will be achieved efficiently and effectively. The purpose of this internship is to determine the effect of HR quality on the employee salary payment compensation system and find out the improvement of employee performance through the provision of compensation systems that have been implemented by the company at PT Primissima. PT Primissima which was formed on June 22, 1971 is a joint venture between the Indonesian Batik Cooperative Association (GKBI) and the Government of the Republic of Indonesia which aims to be able to produce fine batik raw materials, namely Primissima cloth (mori) to meet national needs, which were previously taken through production or imports from China, Japan, and India. The research approach carried out by the author is a qualitative approach. The author's achievement while undergoing an internship was working in the personnel division of PT Primissima. In addition, the author had the opportunity to observe and participate in employee coaching at PT Primissima, and follow a series of batik fabric making processes at PT Primissima. In the midst of uncertain HR quality, it is necessary to conduct careful and strict recruitment. Prospective workers or employees must meet the requirements of the PT Primissima company. One of the concerns when accepting prospective employees is in terms of soft skills and hard skills. Because it is an obstacle of the company PT Primissima at this time. Researchers in carrying out internships feel comfortable and smooth in carrying out work activities in the company where researchers do internships. Researchers received a good response and treatment from PT Primissima. A comfortable work environment makes researchers comfortable when undergoing the internship research process. The obstacles that researchers encounter in this internship activity include the busy staff of the company, so researchers find it difficult if they want to ask questions or discuss